Predicting climate-driven habitat shifting of the Near Threatened Satyr Tragopan (Tragopan satyra; Galliformes) in the Himalayas. (1st October 2018) - Chhetri, Bijoy; Badola, Hemant; Barat, Sudip
Current rates of climatic change will affect the structure and function of community assemblages on Earth. In recent decades, advances in modelling techniques have illuminated the potential effects of various climatic scenarios on biodiversity hotspots, including community assemblages in the Himalayas. These techniques have been used to test the effects of representative concentration pathways (RCPs) AR5-2050, based on future greenhouse gas emission trajectories of climate change scenario/year combinations, on pheasants. Current bioclimatic variables, Miroc-esm, Hadgem2-AO and Gfdl-cm3, in future climate change scenario models, were used to predict the future distribution and the gain/loss of future habitat area, within the Himalayas, of the pheasant, Satyr Tragopon (Tragopan satyra). The results indicate that future climatic conditions may significantly affect the future distribution of Satyr Tragopon and the effectiveness of protective areas (PAs). Using the python based GIS toolkit, SDM projection, regions of high risk under climate change scenarios were identified. To predict the present distribution of the species, environment parameters of bioclimatic variables, red reflectance, blue reflectance, solar azimuth angle, altitude, slope, aspect, NDVI, EVI, VI, and LCLU were used. The forest cover (NDVI) and the canopy cover (EVI), and variables affecting forest structure, namely altitude, slope, solar azimuth angle and Bio7, were the primary factors dictating the present distribution of T. satyra. The predicted trend of habitat shifting of T. satyra in the Himalayas to higher altitudes and latitudes will gradually become more prominent with climate warming.